Pengembangan Media Gambar Untuk Menulis Puisi Kelas X SMA - Asep Perdiansyah; Nurlaksana Eko Rusminto; Iing Sunarti (Universitas Lampung, 2019)
The problem in this research is related to the process of developing visual media for grade X of senior high school students to write poem. The goals of this research are, 1) to create visual media; 2) to describe its eligibility; and 3) to test its effectiveness. The research method used research and development design that adopts eight from ten steps of Borg and Gall research and development procedure. The results show that 1) visual media for grade X senior high school students to write poem has been successfully developed; 2) the eligibility of the visual media is very eligible, which is based on questionnaire from content professional is 92.20%, media professional is 90.10%, and practitioner is 96.80%; 3) Results of the visual media effectiveness in Sugar Group Senior High School, Al-Azhar 3 Senior High School, and MA Asyariyah shows the post-test average is 81.95 and N-gain average score is 0.53. The result is classified as moderate in interpretation criteria.Permasalahan dalam penelitian ini berkaitan dengan pengembangan media gambar untuk menulis puisi siswa kelas X SMA. Tujuan penelitian yakni 1) menghasilkan produk media gambar; 2) mendeskripsikan kelayakan; dan 3) menguji keefektifan. Metode penelitian menggunakan desain penelitian dan pengembangan yang mengadaptasi delapan dari sepuluh langkah dalam prosedur penelitian dan pengembangan menurut Borg and Gall. Hasil penelitian menunjukkan bahwa 1) berhasil dikembangkan media berupa “Media Gambar untuk Menulis Puisi Siswa Kelas X SMA”; 2) kelayakan media gambar berdasarkan angket oleh ahli materi 92,20%, ahli media 90,10%, dan praktisi 96,80% secara keseluruhan dinyatakan “sangat layak” 3) hasil uji keefektifan media gambar pada SMA Sugar Group Lampung Tengah, SMA Al-Azhar 3 Bandar Lampung, dan MA Asyariyah Bandar Lampung dapat disimpulkan skor rata-rata posttest 81,95 dan skor rata-rata N-gain 0,53 termasuk dalam kriteria interpretasi sedang. Kata kunci: media gambar, menulis, puisi